Penggunaan Media Audio Visual Dalam Meningkatkan Kemampuan Mengenal Huruf Hijaiyah Anak Usia 4-5 Tahun - Yolita Desiani; Siti Istiqomah (Fakultas Tarbiyah IIQ Jakarta, 2023)
The purpose of this study was to determine whether the use of auio-visual media can improve the ability to recognize letter hijaiyah in children aged 4-5 years in early childhood Al-Falah Cireundeu South Tangerang City. In this study the authors used descriptive qualitative research by collecting research data through observation, interview instruments, and documentation. With the subjet of research is homeroom teacher and students in Class A early childhood Al-Falah as many as 12 people. While the object of this study is to improve the ability to recognize letters hijaiyah through audio-visual media in early childhood Al-Falah South Tangerang. The results obtained from observation research is the increasing ability of students to recognize letters hijaiyah, children are more interested and enthusiastic in following the learning, because by using audio-visual media children play an active role in the learning process, attracting attention, and also fun for the child